1987
DOI: 10.1111/j.1432-1033.1987.tb13324.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a polysaccharide component of lipopolysaccharide from Pseudomonas aeruginosa IID 1008 (ATCC 27584) as D‐rhamnan

Abstract: Structural studies were carried out on a rhamnose‐rich polysaccharide isolated from the O‐polysaccharide fraction of lipopolysaccharide in Pseudomonas aeruginosa IID 1008 (ATCC 27584) after destruction of the major O‐specific chain by alkaline treatment. The isolated polysaccharide contained rhamnose, 3‐O‐methyl‐6‐deoxyhexose, glucose, xylose, alanine, galactosamine and phosphorus in a molar ratio of 67:6.9:4.3:2.1:1.1:1.0:4.1. Data from analysis involving Smith degradation, methylation, 1H‐NMR spectroscopy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 35 publications
6
42
0
Order By: Relevance
“…Rhamnans have been previously reported to be present in lipopolysaccharide preparations from Pseudomonas aeruginosa (11,12), as well as P. syringae (16,17) and P. cepacia (18). Those from P. aeruginosa occur as minor components of the LPS, and their presence is seen only after the major 0-antigens are selectively hydrolyzed with acid or base; the rhamnans found in the other species are in fact the side chains of the principal LPS's.…”
Section: Nuclear Magnetic Resonance Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Rhamnans have been previously reported to be present in lipopolysaccharide preparations from Pseudomonas aeruginosa (11,12), as well as P. syringae (16,17) and P. cepacia (18). Those from P. aeruginosa occur as minor components of the LPS, and their presence is seen only after the major 0-antigens are selectively hydrolyzed with acid or base; the rhamnans found in the other species are in fact the side chains of the principal LPS's.…”
Section: Nuclear Magnetic Resonance Spectroscopymentioning
confidence: 99%
“…Identities were confirmed by coinjection of standard samples, except for the 3-0-methylhexose, which was identified from its mass spectrum alone, and which was distinguished from a 4 -0 -methylhexose by GC-MS analysis of the alditol-dl acetate^.^ The minor monosaccharides found for the A-PS derived from AK1401 are slightly different from those found in other rhamnanbased polysaccharides of Pseudomonas. For example, Yokota et al (11) found that the polysaccharide from P . aeruginosa ATCC 27584 contained rhamnose, a 6-deoxy-3-0-methylhex6~h e sample of alditol-dl acetates was prepared by Dr. A. Sen (Queen's University); the GC-MS data were acquired by J. Peltier (McMaster University).…”
Section: Nuclear Magnetic Resonance Spectroscopymentioning
confidence: 99%
“…It has been proposed that comparable pathways are used for the biosynthesis of these similar glycoconjugates (3). D-Rhamnose is a rare sugar that is also constituent of the LPS of plant pathogens like Xanthomonas campestris (7), Pseudomonas syringae (8) and of human pathogens, most importantly Pseudomonas aeruginosa (9), Burkholderia cepacia (10), Campylobacter fetus (11), and Helicobacter pylori (12). Recently, a biosynthetic pathway for the nucleotide-activated form of D-rhamnose has been proposed (13).…”
Section: S-layersmentioning
confidence: 99%
“…The reaction of 1,3-di-0-benzylglycerol (9) (13) with 3-0-acetyl-2,4-di-0-benzyl-a-D-rhamnopyranosyl chloride (10) (14) was performed in the presence of silver triflate and powdered, 4 A molecular sieves at -10°C to afford the rhamnopyranoside 11 in 50% yield. 0-Deacetylation of 11 with 0.5% sodium methoxide in methanol at room temperature for 4 h gave 0-(2',4'-di-0-benzyl-a-D-rhamnopyranosy1)-(lf+2)-1,3-di-0-benzylglycerol (12), a glycosyl acceptor, that was in turn glycosylated with 10, again by use of silver triflate and powdered, 4 A molecular sieves, to give the disaccharideglycerol conjugate 13.…”
Section: Synthesis Of Hepta-0-acetyl-0-a-d-rhap-(1+3)-0-a-drhap-(132)mentioning
confidence: 99%